Action! : interviews with directors from classical Hollywood to contemporary Iran - Morris, Gary, 1951- (Anthem art and culture, 2009)
'Action!' draws on the very best published and unpublished interviews of the 'Bright Lights Film Journal', and contains many gems, including the last ever interview given by Francois Truffaut, four months before he died.